Bridging knowledge and conservation in Pichavaram mangroves: A multi-stakeholder study - Harini, B; Suresh, K D; Saravanakumar, V; Uma, K; Balaji, K; Selvi, D (Plant Science Today, 2025)
Mangrove ecosystems play a vital role in coastal protection, climate regulation and supporting livelihoods, yet they remain among the most threatened ecosystems globally. This study assesses the awareness levels and perceptions of primary stakeholder groups-namely residents, fishermen and visitors-regarding the ecological significance, prevailing status and key determinants affecting the Pichavaram mangrove ecosystem in Tamil Nadu, India. Using a structured questionnaire, data were collected from 360 respondents across two panchayats adjacent to the mangrove forest. Statistical and descriptive analyses indicated that provisioning services, such as food and fuelwood, were widely recognized-especially among fishermen and residents-whereas awareness of supporting and regulating services, including nutrient cycling and climate change mitigation, was comparatively limited. Perceptions of the ecosystem varied, with many recognizing degradation, while others noted post-cyclone improvements linked to community conservation initiatives. Climate change impacts, including prolonged saline water intrusion and seedling mortality, were acknowledged by only a minority of respondents, reflecting limited awareness. Nevertheless, a large majority across all stakeholder groups recognized the broader ecological and societal consequences of mangrove loss. The findings highlight the critical need for participatory conservation strategies that integrate local knowledge and address awareness gaps to enhance the sustainable management of mangrove ecosystems. The study offers valuable insights for policymakers, conservationists and development planners seeking to align community engagement with ecological restoration efforts.